A STUDY ON IMPACT OF FACTORS INFLUENCING EMPLOYEE ATTRITION RATE IN IT SECTOR – WOMEN EMPLOYEES PERSPECTIVE - SYED, Dr. SHAIK MAHABOOB (The journal of contemporary issues in business and government, 2022)
Management of employee turnover is very essential condition of human resource management. Hiring the right people is the biggest challenge that HR department faces today. Sometimes candidates are not proficient enough for the job but they say yes to impress the interviewer to get the job, but after sometimes they realize that there is no match between them and job, so they start looking for another option. Employee Retention has contributed substantially to the economic power of the company, but they face the problem of employee turnover that affects the organization because if the turnover of employees increases in the organization than it will affect the productivity of the organization. So, to improve the productivity and performance of the organization current study is conducted. The current study is an attempt to identify the impact of factors (Organizational, HR, Personal and Job-related) on the turnover intentions amongst the employee's in Indian IT Sector. Data was collected from 660 women employee's working in Indian IT Sector. Primary data is collected from five major IT companies i.e. Wipro, Infosys, HCL, Accenture and HCL. Various dimensions of both the constructs are available in the literature but selected dimensions of both the constructs are used for drawing inferences that help organizations in identifying factors that affect turnover intentions.